2014
DOI: 10.1136/bjsports-2014-093494.264
|View full text |Cite
|
Sign up to set email alerts
|

Are Clinical Measures of Cervical Spine Strength and Cervical Flexor Endurance Risk Factors for Concussion in Elite Youth Ice Hockey Players?

Abstract: Background Symptoms of dizziness, neck pain and headaches have previously been identified as risk factors for concussion. Clinical measures associated with these symptoms have not previously been evaluated as risk factors for concussion. Objectives To evaluate clinical measures of cervical endurance and strength as risk factors for concussion in elite youth ice hockey players. Design Prospective cohort study. Setting Community ice rinks and Sport Medicine Clinic. Participants Bantam (12-14 years) and Midget (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…105 Possible explanations for the increased risk include altered neuromuscular control, sensorimotor control, balance, or cervical spine strength. 101 High school athletes with lower neck strength may have a greater risk of concussion. 19 In youth ice hockey players, an increased risk of concussion has been reported in players who did not meet the Canadian recommendations for daily physical activity ( activity) in the 6 weeks prior to study entry.…”
Section: Intrinsic Risk Factors For Concussionmentioning
confidence: 99%
“…105 Possible explanations for the increased risk include altered neuromuscular control, sensorimotor control, balance, or cervical spine strength. 101 High school athletes with lower neck strength may have a greater risk of concussion. 19 In youth ice hockey players, an increased risk of concussion has been reported in players who did not meet the Canadian recommendations for daily physical activity ( activity) in the 6 weeks prior to study entry.…”
Section: Intrinsic Risk Factors For Concussionmentioning
confidence: 99%
“…If one or more of these systems provide inaccurate information about spatial location, alteration in balance and dizziness may result due to mismatching of sensory information. Additionally, dysfunction of these systems may persist and may alter risk of future concussion 17 18…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the protective role of greater neck strength in sports have shown mixed results. Neck strength was not found to be predictive of concussion risk for ice hockey players [ 26 ]. However, a small study (n = 17) of adolescent female soccer players found that greater neck strength is negatively correlated with head acceleration during heading [ 9 ], and a large study (n = 6,704) of male and female adolescent basketball, soccer, and lacrosse athletes found that for every 1 pound increase in neck strength, the odds of concussion decreased by 5% [ 27 ].…”
Section: Introductionmentioning
confidence: 99%